Effects of the endogenous cannabinoid anandamide on voltage‐dependent sodium and calcium channels in rat ventricular myocytes. (July 2014) - Al Kury, Lina T; Voitychuk, Oleg I; Yang, Keun‐Hang Susan; Thayyullathil, Faisal T; Doroshenko, Petro; Ramez, Ali M; Shuba, Yaroslav M; Galadari, Sehamuddin; Howarth, Frank Christopher; Oz, Murat
<x xml:space="preserve">Abstract</x> Background and Purpose The endocannabinoid anandamide (N‐arachidonoyl ethanolamide; AEA) exerts negative inotropic and antiarrhythmic effects in ventricular myocytes. Experimental Approach Whole‐cell patch‐clamp technique and radioligand‐binding methods were used to analyse the effects of anandamide in rat ventricular myocytes. Key Results In the presence of 1–10 μM AEA, suppression of both Na+ and L‐type Ca2+ channels was observed. Inhibition of Na+ channels was voltage and Pertussis toxin (PTX) – independent. Radioligand‐binding studies indicated that specific binding of [3H] batrachotoxin (BTX) to ventricular muscle membranes was also inhibited significantly by 10 μM metAEA, a non‐metabolized AEA analogue, with a marked decrease in Bmax values but no change in Kd. Further studies on L‐type Ca2+ channels indicated that AEA potently inhibited these channels (IC50 0.1 μM) in a voltage‐ and PTX‐independent manner. AEA inhibited maximal amplitudes without affecting the kinetics of Ba2+ currents. MetAEA also inhibited Na+ and L‐type Ca2+ currents. Radioligand studies indicated that specific binding of [3H]isradipine, was inhibited significantly by metAEA. (10 μM), changing Bmax but not Kd. Conclusion and Implications Results indicate that AEA inhibited the function of voltage‐dependent Na+ and L‐type Ca2+ channels in rat ventricular myocytes, independent of CB1 and CB2 receptor activation.